2018
DOI: 10.5037/jomr.2018.9202
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic Rehabilitation of the Partially Edentulous Atrophic Posterior Mandible with Short Implants (≤ 8 mm) Compared with the Sandwich Osteotomy and Delayed Placement of Standard Length Implants (> 8 mm): a Systematic Review

Abstract: ObjectivesTest the hypothesis of no difference in prosthetic rehabilitation of the partially edentulous atrophic posterior mandible with short implants (≤ 8 mm) compared with the sandwich osteotomy and delayed placement of standard lengths implants (> 8 mm).Material and MethodsA MEDLINE (PubMed), Embase and Cochrane library search in combination with a hand-search was conducted by including studies published in English. No year of publication restriction was applied.ResultsSix randomized controlled trials char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…This up‐to‐date review found that implants shorter than 7 mm can be as effective as standard‐length implants in augmented sites for the rehabilitation of partially edentulous and posterior atrophic jaws. As compared to previous reviews that investigated the performance of SH implants, 3,4,6,7,12,17,23,24,26,27,93‐97 the present one counted on a wider database and a longer follow‐up, and only focused on RCTs comparing SH implants inserted in edentulous atrophic jaws and ST implants in reconstructed atrophic jaws, of comparable residual bone dimension. In fact, several studies were excluded because the residual bone dimension differed between test and control group (eg, SH implants in atrophic jaws vs ST implants in non‐atrophic edentulous jaws), or ST implants were inserted without augmentation procedures, or SH implants were inserted with concomitant augmentation procedures.…”
Section: Discussionmentioning
confidence: 99%
“…This up‐to‐date review found that implants shorter than 7 mm can be as effective as standard‐length implants in augmented sites for the rehabilitation of partially edentulous and posterior atrophic jaws. As compared to previous reviews that investigated the performance of SH implants, 3,4,6,7,12,17,23,24,26,27,93‐97 the present one counted on a wider database and a longer follow‐up, and only focused on RCTs comparing SH implants inserted in edentulous atrophic jaws and ST implants in reconstructed atrophic jaws, of comparable residual bone dimension. In fact, several studies were excluded because the residual bone dimension differed between test and control group (eg, SH implants in atrophic jaws vs ST implants in non‐atrophic edentulous jaws), or ST implants were inserted without augmentation procedures, or SH implants were inserted with concomitant augmentation procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Further, as there are still insufficient data that could determine the optimal treatment, whether it would be rehabilitation using short implants or bone augmentation that would allow the use of longer implants, clinicians often face problematic situations [3]. However, some studies suggest that short implants may be more advantageous than longer implants placement following bone augmentation because of the reduced number of complications [7,8,11,12]. In comparison with sandwich osteotomy and delayed implant placement, prosthetic rehabilitation of the partially edentulous atrophic mandible with short implants has been shown to have a comparable survival rate [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies suggest that short implants may be more advantageous than longer implants placement following bone augmentation because of the reduced number of complications [7,8,11,12]. In comparison with sandwich osteotomy and delayed implant placement, prosthetic rehabilitation of the partially edentulous atrophic mandible with short implants has been shown to have a comparable survival rate [11]. Moreover, short implants placed in an atrophic ridge and long implants placed after alveolar bone augmentation have been reported to present similar short-term peri-implant alveolar bone loss, regardless of the arch [7].…”
Section: Introductionmentioning
confidence: 99%
“…It also provides a wide range of retentive possibilities, even for non‐parallel implants . With a low vertical profile of 2.1 mm and diameter of 4.4 mm, the OT Equator abutment (Rhein83) fits into patients mouths with vertical space limitations; it can also be placed over standard‐length (≥8 mm) and short (<8 mm) implants . In addition, this component can be applied to temporary and definitive prostheses, by using the same anchoring system.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 With a low vertical profile of 2.1 mm and diameter of 4.4 mm, the OT Equator abutment (Rhein83) fits into patients mouths with vertical space limitations; it can also be placed over standard-length (≥8 mm) and short (<8 mm) implants. 10,12 In addition, this component can be applied to temporary and definitive prostheses, by using the same anchoring system. Despite the advantages, this new abutment system is not indicated for single crowns since it does not present anti-rotational components.…”
mentioning
confidence: 99%